A rhodamine-based fluorescent probe for Fe3+: synthesis, theoretical calculation and bioimaging application. Issue 19 (29th April 2019) - Cheng, Zhao; Zheng, Lei; Xu, Hao; Pang, Long; He, Hao
Abstract : A rhodamine-based fluorescent probeJ1 with low cytotoxicity and characteristic fluorescence imaging of intracellular Fe 3+ in living cells L929. Abstract : A novel rhodamine-based fluorescent probe was designed and synthesized. Its metal ion selectivity was illuminated by the highly specific recognition of the probe towards Fe 3+ over other metal ions; moreover, the color change in the recognition process of Fe 3+ could be used for its "naked-eye" detection in an aqueous environment. In addition, a theoretical calculation was performed to reveal the possible reaction mechanism between the probe and Fe 3+ . The fluorescent imaging of Fe 3+ in living cells further suggested future applications of the probe for instant Fe 3+ detection in a clinical diagnosis and dynamic tracking of Fe 3+ in biological systems.